Obesity and gynaecological and obstetrical conditions: an umbrella review of the literature - kalliala,I; Markozannes,G; Gunter,M; Paraskevaidis,E; Gabra,H; Mitra,A; terzidou,V; Martin-Hirsch,P; Tsilidis,K; Kyrgiou,M (British Medical Journal, 2017)
Objective To study the strength and validity of associations between adiposity and risk of any type of obstetric or gynaecological conditions.Design An umbrella review of meta-analyses.Data sources PubMed, Cochrane database of systematic reviews, manual screening of references for systematic reviews or meta-analyses of observational and interventional studies evaluating the association between adiposity and risk of any obstetrical or gynaecological outcome.Main outcomes Meta-analyses of cohort studies on associations between indices of adiposity and obstetric and gynaecological outcomes.Data synthesis Evidence from observational studies was graded into strong, highly suggestive, suggestive, or weak based on the significance of the random effects summary estimate and the largest study in the included meta-analysis, the number of cases, heterogeneity between studies, 95% prediction intervals, small study effects, excess significance bias, and sensitivity analysis with credibility ceilings. Interventional meta-analyses were assessed separately.Results 156 meta-analyses of observational studies were included, investigating associations between adiposity and risk of 84 obstetric or gynaecological outcomes. Of the 144 meta-analyses that included cohort studies, only 11 (8%) had strong evidence for eight outcomes: adiposity was associated with a higher risk of endometrial cancer, ovarian cancer, antenatal depression, total and emergency caesarean section, pre-eclampsia, fetal macrosomia, and low Apgar score. The summary effect estimates ranged from 1.21 (95% confidence interval 1.13 to 1.29) for an association between a 0.1 unit increase in waist to hip ratio and risk endometrial cancer up to 4.14 (3.61 to 4.75) for risk of pre-eclampsia for BMI >35 compared with <25. Only three out of these eight outcomes were also assessed in meta-analyses of trials evaluating weight loss interventions. These interventions significantly reduced the risk of caesarean section and pre